'Let's go outside': Icelandic teachers' views of using the outdoors. Issue 4 (3rd July 2016) - Norðdahl, Kristín; Jóhannesson, Ingólfur Ásgeir
Abstract : This article discusses the views of 25 Icelandic preschool and compulsory school teachers who were interviewed on the role of the outdoor environment in children's learning. The teachers reported not being afraid to take children outside. These teachers valued the learning potentials of the outdoors more than they feared the possible risks. They believed that the outdoors could provide opportunities for (a) enhancing children's play and learning (b) promoting children's health, well-being, and courage, and (c) affecting children's views, knowledge, and actions towards sustainability.